2007
DOI: 10.1080/00365520600965749
|View full text |Cite
|
Sign up to set email alerts
|

Feeding and colonic distension provoke altered autonomic responses in irritable bowel syndrome

Abstract: IBS patients demonstrated altered autonomic responses to feeding and colonic distension. Further studies should determine whether these alterations could explain the postprandial exacerbation of symptoms in IBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 17 publications
0
33
1
Order By: Relevance
“…The lack of difference in ANS measures between IBS and controls at baseline differs from most previous HRV analysis findings which show IBS patients having higher cardiosympathetic tone and/or lower cardiovagal tone compared with healthy controls . Our main finding of ANS blunting in IBS in response to visceral stressor differs from the literature which generally shows greater cardiosympathetic activity in IBS patients during and after both rectal/colonic distensions and meals compared with controls.…”
Section: Discussioncontrasting
confidence: 99%
“…The lack of difference in ANS measures between IBS and controls at baseline differs from most previous HRV analysis findings which show IBS patients having higher cardiosympathetic tone and/or lower cardiovagal tone compared with healthy controls . Our main finding of ANS blunting in IBS in response to visceral stressor differs from the literature which generally shows greater cardiosympathetic activity in IBS patients during and after both rectal/colonic distensions and meals compared with controls.…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have previously reported that IBS patients show various alterations in their autonomic, immunologic and visceral response to food intake. 11,[15][16][17][18][19][20][21][22]29,30 However, to the best of our knowledge this is one of the first studies to propose a meal as a way to induce GI symptoms in IBS patients and compare their symptom responses to healthy controls, with the intention to create a tool for disease evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated that postprandial GI disorders in IBS patients might be associated with cellular immune function along the neuroendocrine-immune axis [152] . Furthermore, altered autonomic responses after a meal might cause exacerbated postprandial symptoms in IBS patients [153] .…”
Section: Dietary Factorsmentioning
confidence: 99%